Partiality towards women of color because of their gender role in Roque Moreno by Teresa González de Fanning - Santoni Morro, Isis A. (2022)
This article will analyze the biased position that the writer Teresa González de Fanning has with her character Chavelita, who is a woman of color that is part of the nineteenth-century novel Roque Moreno. We propose that this bias is because Chavelita fulfills the feminine-domestic ideal that the writer defended and professed from her position as an enlightened woman.